Which Intelligence is Most Important in Forming the Entrepreneurial Spirit? - Imas Soemaryani (Jurnal Bisnis Manajemen, 2017)
The role of entrepreneurs becomes more influential in the current business world. Due to lack of entrepreneurial spirit, many entrepreneurs experience unsuccessful result in their entrepreneurship journey. Entrepreneurial spirit results from a combination of someone’s hereditary factors, experience, and environment. This gives HRM wide room of discussion to find suitable stimulating factors to improve entrepreneurial spirit. Growing evidence shows various intelligence can contribute to someone’s entrepreneurial spirit including intellectual quotient, emotional quotient, spiritual quotient, social quotient, and adversity quotient. This research aims to examine which of each quotient has the most influential factor to the entrepreneurial spirit. This study was conducted using 30 small-and-medium-scale fashion entrepreneurs in Bandung and analyzed using weighting approach and ranking method. Based on the findings, this research suggests that SQ (Spiritual Quotient), followed by adversary quotient, has the strongest influence in shaping the entrepreneurial spirit.